Data from: Heterozygosity at neutral and immune loci is not associated with neonatal mortality due to microbial infection in Antarctic fur seals - Litzke, Vivienne; Ottensmann, Meinolf; Forcada, Jaume; Heitzmann, Louise; Hoffman, Joseph Ivan (Zenodo, 2019)
Numerous studies have reported correlations between the heterozygosity of genetic markers and fitness. These heterozygosity fitness correlations (HFCs) play a central role in evolutionary and conservation biology, yet their mechanistic basis remains open to debate. For example, fitness associations have been widely reported at both neutral and functional loci, yet few studies have directly compared the two, making it difficult to gauge the relative contributions of genome-wide inbreeding and functional genetic variation to fitness. Here, we compared the effects of neutral and immune gene heterozygosity on death from bacterial infection in Antarctic fur seal (Arctocephalus gazella) pups. We specifically developed a panel of 13 microsatellites from expressed immune genes and genotyped these together with 48 neutral loci in 234 individuals, comprising 39 pups that were classified at necropsy as having most likely died of bacterial infection together with a five times larger matched sample of healthy surviving pups. Identity disequilibrium quantified from the neutral markers was positive and significant, indicative of variance in inbreeding within the study population. However, multilocus heterozygosity did not differ significantly between healthy and infected pups at either class of marker, and little evidence was found for fitness associations at individual loci. These results support a previous study of Antarctic fur seals that found no effects of heterozygosity at nine neutral microsatellites on neonatal survival, and thereby help to refine our understanding of how HFCs vary across the life cycle. Given that non-significant HFCs are underreported in the literature, we also hope that our study will contribute towards a more balanced understanding of the wider importance of this phenomenon. Supplementary Table S1 2362 microsatellite loci identified from the Antarctic fur seal transcriptome assembly that consist of a minimum of five short tandem repeats with perfect di-, tri- and tetranucleotide motifs. ...